2010
DOI: 10.1080/08853908.2011.532047
|View full text |Cite
|
Sign up to set email alerts
|

Trade Effects of Anti-dumping in India: Who Benefits?

Abstract: This article assesses the trade effects of anti-dumping (AD) duties levied on 177 (8-digit) products by India during the period 1994 to June 2001. A panel regression has been applied to quantify the effects of AD actions on import volumes, values, and prices. It finds that the investigation effects of AD actions are not substantial. The imposition of AD duties restrains trade (both volume and value) and raises import prices. While trade effects start dissipating in subsequent years, import prices from both na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…Sandkamp (2020) indicates that trade destruction effects may be larger than previously thought for the European Union (EU). Other studies have found qualitatively similar results for developed countries (Baran, 2015; Staiger & Wolak, 1994) and developing countries (Aggarwal, 2010; Lee et al, 2013; Park, 2009). Apart from at the national level, several existing studies document AD measures’ effects on the number of exporters and exporters’ profits, productivity, market value and export volume at the firm level (Chandra & Long, 2013; Lu et al, 2018; Schiavo et al, 2021).…”
Section: Introductionsupporting
confidence: 60%
“…Sandkamp (2020) indicates that trade destruction effects may be larger than previously thought for the European Union (EU). Other studies have found qualitatively similar results for developed countries (Baran, 2015; Staiger & Wolak, 1994) and developing countries (Aggarwal, 2010; Lee et al, 2013; Park, 2009). Apart from at the national level, several existing studies document AD measures’ effects on the number of exporters and exporters’ profits, productivity, market value and export volume at the firm level (Chandra & Long, 2013; Lu et al, 2018; Schiavo et al, 2021).…”
Section: Introductionsupporting
confidence: 60%
“…Park (2009) investigated the impacts of China's antidumping activities on trade and trade patterns, with significant trade depressing and trade diversion effects found. Aggarwal (2010) studied trade effects of antidumping duties levied by India over the 1994-2001 period based on difference generalized method of moments (DIF-GMM) method. Empirical results showed evidence of both restrained trade (both volume and value) and raised import prices.…”
Section: Introductionmentioning
confidence: 99%
“…Carter and Gunning-Trant (2010) found neither investigation nor trade diversion effects in association with US agricultural AD measures, while Wang and Reed (2015) revealed that US AD duties instigated trade deflection of shrimp products to non-named third markets. Aggarwal (2010) showed that only the big firms benefited from protective AD measures of India. The study also revealed that developing countries suffer significant losses from Indian AD measures, while there is no evidence of trade destruction effects for developed countries.…”
Section: Literature Reviewmentioning
confidence: 99%